LEADERSHIP STYLE OF WOMEN IN EDUCATION: A CASE STUDY OF SCHOOLS IN JAKARTA - Kristanty, Desy Natalia; Rumambi, Freddy J; Tangkudung, Audrey G; Sompi, Pingkan Luciawati (Sosiohumaniora, 2026)
This study aims to examine the influence of women leadership styles in educational environments on the character building. The study uses a qualitative approach by comparing the leadership of principals in two junior high schools in the context of character education, namely SMP GIS and SMP Negeri 99 Jakarta. Data were collected through in-depth interviews, observations, and literature studies. Data were analyzed using the Miles & Huberman (1992) approach, which consists of 4 stages, namely: 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusions/verification. The results of the study indicate that women principals: 1) apply a transformational leadership style, 2) become a source of collective inspiration and motivation for teachers and students, and 3) build emotional without losing professional authority. Fundamental differences are seen in the reflection of the success of character application and problem handling. By applying a transformational leadership style, women principals are able to create a conducive educational climate, encouraging the development of character values in students such as responsibility, discipline, empathy, and independence. A transformational leadership style that emphasizes empathy, participation, and inspiration enables women principals to become strong moral role models and shape a positive school culture. This research strengthens the transformational leadership style theoretically and practically, because it is able to address the challenges of character building for the younger generation, especially amidst the dynamics of the digital era and Generation Z culture. Therefore, it is recommended that the Government and Educational Institutions provide greater support to women principals to improve their capabilities.